Statslig neutralitet og uenighed om kendsgerninger - Nielsen, Morten Ebbe Juul; Andersen, Martin Marchman (Politik, 2014)
The main question pursued in this paper concerns whether (political) neutrality of justi cation – i.e., the idea that the state ought to be neutral vis-a-vis conceptions of the good – implies that the state ought to be neutral vis-a-vis (at least certain) forms of empirical facts. We argue that this is not the case. Mainstream liberal neutralism does not advocate any form of neutrality regarding facts. However, it might be claimed that it is unclear why non-neutrality regarding facts does not imply some form of disrespect for citizens insofar as non-neutrality regarding conceptions of the good can imply such disrespect, according to neutralists. We argue that non-neutrality regarding facts does not necessarily imply disrespect, and hence that the ideal of respecting citizens is not necessarily compromised by state non-neutrality regarding facts. Hence, liberal neutrality of justi cation is not compromised by state non-neutrality regarding facts.